2007
DOI: 10.1902/jop.2007.060221
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival Chlorhexidine Varnish Administration as an Adjunct to Same‐Day Full‐Mouth Root Planing. I. Clinical Observations

Abstract: The outcome of same-day full-mouth root planing may benefit from the subgingival administration of a highly concentrated chlorhexidine varnish, at least in terms of pocket reduction in initially deep sites (>or=7 mm).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…All patients gave informed consent. Demographic details and study design are described in an accompanying paper reporting clinical observations 20 . Briefly, subjects in the control group received full‐mouth SRP completed in 12 hours using an ultrasonic scaler and standard periodontal curets, including polishing and oral hygiene instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients gave informed consent. Demographic details and study design are described in an accompanying paper reporting clinical observations 20 . Briefly, subjects in the control group received full‐mouth SRP completed in 12 hours using an ultrasonic scaler and standard periodontal curets, including polishing and oral hygiene instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies indicated beneficial clinical effects when 35% (weight/volume [w/v]) chlorhexidine (CHX) varnish † was applied subgingivally as an adjunct to SRP performed in two stages 17,18 . Similar, yet less marked, effects were shown using this antimicrobial agent adjunctive to same‐day full‐mouth root planing 19,20 . The hypothesis behind these treatment strategies lies in the ability of the varnish to increase/prolong microbiological improvements of SRP.…”
mentioning
confidence: 99%
“…However, at present, chlorhexidine (CHX) represents the gold standard among the disinfectants used for the treatment of periodontal and peri-implant infections. Chlorhexidine is active against many microbial species [13][14][15], but it may exert some cytotoxic effect as shown in some in vitro studies [16,17]. Furthermore, the antimicrobial activity of chlorhexidine is strongly reduced in the presence of serum [18], which in turn, limits its effectiveness in the subgingival environment.…”
mentioning
confidence: 99%
“…To enhance the efficacy of non-surgical therapy a chemo-mechanical treatment concept was introduced based on sequential SRP and the adjunctive subgingival administration of 35% CHX varnish[5] and subgingival placement of a biodegradable CHX chip,[6] which biodegrades and releases CHX within the pocket over 7-10 days maintaining an average concentration in the GCF greater than 12 mg/ml for 8 days.…”
Section: Introductionmentioning
confidence: 99%